TARGETED APPROACHES OF THE TEACHER IN STUDENTS' UNDERSTANDING OF HISTORICAL REALITY - Usmanaliyeva Risolat (Western European Studies, 2024)
The article examines the science of history and its essence, historical reality, as well as what works and means are necessary for students to understand and feel historical reality not only during the lesson, but also in the general social environment. It also reveals our history, the great material and spiritual heritage left to us by our ancestors, our current opportunities, our future dreams and prospects, as well as pedagogical tasks on the way to achieving them.
Keywords: thinking; creative thinking; socialization; forecast